Enhancing students’ understanding of Pancasila as a state ideology for anti-corruption education - Raihan Raihan; Irvan Hardianto; Dinda Rahmi Istifara; Aulia Mawwaddah; Kevin Yuhedi Firdaus; Tifanny Syentia Putri; Dwi Rahmadani; Sepriani Estasia; Cahaya Adinda Rizki Zulmi; Silvi Fakhriano; Al Hafiz Situmorang (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2025)
Corruption remains one of the most serious threats to Indonesia’s social, economic, and moral development, undermining public trust and national integrity. Addressing this issue requires comprehensive efforts, including preventive measures implemented through early age education. This community service program was conducted as an educational intervention to strengthen elementary school students’ understanding of anti-corruption values grounded in Pancasila, the state ideology. The program was implemented based on the rationale that character education, particularly integrity and honesty, must be cultivated early to build a generation resistant to corrupt behavior. The primary objective of this activity was to enhance students’ awareness and internalization of integrity values in their daily lives. The program employed interactive training methods, including group discussions, question-and-answer sessions, and simple educational games, to actively engage students and facilitate meaningful learning experiences. The findings indicate that approximately 90% of participants demonstrated an improved understanding of integrity values and showed the ability to apply these principles in everyday situations. Overall, this community service activity highlights the strategic role of character-based anti-corruption education in shaping morally responsible young citizens and suggests that similar programs could be expanded to other regions to generate broader societal impact.   Abstrak Korupsi salah satu permasalahan serius yang mengancam pembangunan, kesejahteraan, serta moral bangsa Indonesia karena berdampak pada melemahnya kepercayaan publik dan nilai-nilai sosial. Upaya pencegahan korupsi perlu dilakukan secara komprehensif, salah satunya melalui pendidikan sejak usia dini. Kegiatan pengabdian kepada masyarakat ini dilaksanakan sebagai bentuk kontribusi akademik dalam menanamkan nilai-nilai antikorupsi kepada murid sekolah dasar yang berlandaskan pada Pancasila sebagai ideologi negara. Tujuan pengabdian ini adalah meningkatkan pemahaman dan kesadaran murid terhadap pentingnya nilai integritas, kejujuran, dan tanggung jawab dalam kehidupan sehari-hari. Pengabdian ini dilatarbelakangi oleh pentingnya pendidikan karakter sejak dini sebagai fondasi pembentukan generasi muda yang berakhlak dan memiliki ketahanan moral terhadap perilaku koruptif. Metode yang digunakan dalam kegiatan ini bersifat interaktif dan partisipatif, meliputi diskusi kelompok, tanya jawab, serta permainan edukatif yang disesuaikan dengan karakteristik murid. Hasil pengabdian menunjukkan bahwa sekitar 90% murid mengalami peningkatan pemahaman terhadap nilai-nilai antikorupsi dan mampu mengaplikasikannya dalam aktivitas sehari-hari. Temuan ini menegaskan pentingnya penguatan pendidikan karakter berbasis Pancasila sebagai strategi efektif dalam pencegahan korupsi sejak dini. Kata Kunci: murid sekolah dasar, nilai Pancasila; pendidikan antikorupsi; pendidikan karakter